Free riding or just surfing : applied ethics. - Aboobaker, Yusuf (My University, 2014)
The paper in the broadest sense looks to the usage of the internet and our obligations if at all any, there to be. We use the case of Wikipedia as a reference site. We used literature from the free rider problem, we deconstructed the literature into relevant elements, and then built a framework to which the case of Wikipedia can be applied. The results of the application shows, at times, users are not merely surfing when they browse the internet, they are free riding and as such may be morally liable to those internet sites.
Keywords: Wikipedia.; Internet--Moral and ethical aspects.; Internet users.